Implementing Survivorship Care Plans for Colon Cancer Survivors - Mayer, Deborah K. (Oncol Nurs Forum, 2014)
PURPOSE/OBJECTIVES: To evaluate the feasibility, usability, and satisfaction of a survivorship care plan (SCP) and identify the optimum time for its delivery during the first 12 months after diagnosis. DESIGN: Prospective, descriptive, single-arm study. SETTING: A National Cancer Institute–designated cancer center in the southeastern United States. SAMPLE: 28 nonmetastatic colon cancer survivors within the first year of diagnosis and their primary care physicians (PCPs). METHODS: Regular screening identified potential participants who were followed until treatment ended. An oncology certified nurse developed the JourneyForward™ SCP, which then was delivered to the patient by the oncology nurse practitioner (NP) during a routine follow-up visit and mailed to the PCP. MAIN RESEARCH VARIABLES: Time to complete, time to deliver, usability, and satisfaction with the SCP. FINDINGS: During one year, 75 patients were screened for eligibility, 34 SCPs were delivered, and 28 survivors and 15 PCPs participated in the study. It took an average of 49 minutes to complete a surgery SCP and 90 minutes to complete a surgery plus chemotherapy SCP. Most survivors identified that before treatment ended or within the first three months was the preferred time to receive an SCP. CONCLUSIONS: The SCPs were well received by the survivors and their PCPs, but were too time and labor intensive to track and complete. IMPLICATIONS FOR NURSING: More work needs to be done to streamline processes that identify eligible patients and to develop and implement SCPs. Measuring outcomes will be needed to demonstrate whether SCPs are useful or not.